Compelled and constrained migration: restrictions to migration agency in the Marshall Islands - Roland, Hugh B. (Frontiers in Climate, 2023)
Migration as adaptation implies agency, yet environmental and non-environmental factors and their interactions may limit the availability of adaptation options, including migration. This study investigates migration agency in the Marshall Islands, particularly the role of geographic isolation and climate change. Interviews with internal migrants living in Majuro and members of government and civil society reveal how social, economic, cultural, and environmental factors shape migration contexts. Results suggest that geographic isolation-related factors may increase likelihoods of simultaneously more compelled and more constrained moves, particularly as climate change impacts increase. Climate change-related impacts on resource-dependent livelihoods may compel migration in search of new economic opportunities. However, worsening environmental conditions may also exacerbate cost-related migration constraints by reducing the resources available to support migration.